Resin composition for circuit board, molded product for circuit board, laminate for circuit board, and circuit board

By using a resin composition of melt-processable fluororesin and boron nitride particles in the circuit substrate, the problems of large energy loss and insufficient heat dissipation during use in the high-frequency band domain are solved, and low dielectric characteristics and excellent heat dissipation are achieved.

CN114026170BActive Publication Date: 2025-04-18DAIKIN INDUSTRIES LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202080045880.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-07-16
Filing Date
2020-07-10
Publication Date
2025-04-18
Estimated Expiration
2040-07-10

AI Technical Summary

Technical Problem

The existing circuit substrates have problems such as large energy loss and insufficient heat dissipation when used in the high-frequency band domain.

Method used

Using a resin composition containing melt-processable fluororesin and boron nitride particles, the dielectric properties and thermal conductivity of the resin composition are optimized by adjusting the composition and particle size distribution.

Benefits of technology

It achieves low dielectric characteristics and excellent heat dissipation, is suitable for high-frequency circuit substrates, reduces energy loss during use in the high-frequency band domain, and improves heat dissipation performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure GDA0003426126520000151
    Figure GDA0003426126520000151
Patent Text Reader

Abstract

Provided are a resin composition for a circuit board having low dielectric properties and excellent heat dissipation. A resin composition for a circuit board, comprising a melt-processable fluororesin and boron nitride particles.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a resin composition for a circuit board, a molded body for a circuit board, a laminate for a circuit board, and a circuit board. Background Art

[0002] Circuit boards used in electric equipment, electronic equipment, communication equipment, and the like are required to have various properties depending on their use.

[0003] Patent Document 1 discloses a dielectric resin composition comprising isotactic polypropylene and anisotropic magnesium oxide particles.

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: Japanese Patent Application Publication No. 2015-168731 Summary of the invention

[0007] Problems to be solved by the invention

[0008] An object of the present invention is to provide a resin composition for a circuit board, a molded product for a circuit board, a laminate for a circuit board, and a circuit board having low dielectric properties and excellent heat dissipation.

[0009] Means for solving problems

[0010] The present invention relates to a resin composition for a circuit board comprising a melt-processable fluororesin and boron nitride particles.

[0011] Preferably, the melt-processable fluororesin accounts for 35 to 70% by mass, the boron nitride particles account for 30 to 65% by mass, and the resin composition has a melt flow rate of 5.0 g / 10 minutes or more.

[0012] In the boron nitride particles, the ratio (b) of particles having a particle size of 24.6 to 29.4 μm to the ratio (a) of particles having a particle size of 14.6 to 20.6 μm ((b) / (a)) is preferably 1.0 or more.

[0013] Preferably, the proportion (a) of the boron nitride particles having a particle size of 14.6 to 20.6 μm is 5.0% or less.

[0014] Preferably, the proportion (b) of the boron nitride particles having a particle size of 24.6 to 29.4 μm is 10.0% or less.

[0015] The melt-processable fluororesin is preferably at least one selected from the group consisting of tetrafluoroethylene / perfluoro(alkyl vinyl ether) copolymers, tetrafluoroethylene / hexafluoropropylene copolymers, and ethylene / tetrafluoroethylene copolymers.

[0016] The present invention also relates to a molded article for a circuit board obtained from the above resin composition.

[0017] The present invention also relates to a laminate for a circuit board, comprising a metal layer (A1) and a layer (B) formed from the above-mentioned resin composition.

[0018] The present invention also relates to a circuit board comprising a metal layer (A2) and a layer (B) formed from the above-mentioned resin composition.

[0019] The circuit board is preferably a printed wiring board.

[0020] The circuit substrate is preferably a high-frequency circuit substrate.

[0021] The above-mentioned circuit substrate is also preferably a circuit substrate for a fifth-generation mobile communication system.

[0022] Effects of the Invention

[0023] According to the present invention, a resin composition for a circuit board, a molded product for a circuit board, a laminate for a circuit board, and a circuit board having low dielectric properties and excellent heat dissipation can be provided. DETAILED DESCRIPTION

[0024] Hereinafter, the present invention will be described in detail.

[0025] The present invention relates to a resin composition for a circuit board comprising a melt-processable fluororesin and boron nitride particles.

[0026] The resin composition of the present invention contains boron nitride particles. Boron nitride is a filler with a low dielectric loss tangent. By containing the boron nitride particles, the resin composition can reduce the dielectric loss tangent while maintaining the low dielectric constant of the fluororesin, and is therefore suitable for use in circuit boards.

[0027] In recent years, there is a tendency to use higher frequency bands in electrical equipment, electronic equipment, communication equipment, etc. Therefore, the circuit substrates used in these devices are also required to have excellent electrical properties for high frequency bands. In particular, low dielectric properties (low dielectric constant and dielectric loss tangent) are required to reduce transmission loss.

[0028] In addition to the low dielectric property, the resin composition of the present invention has excellent heat dissipation due to its good thermal conductivity.

[0029] Since electronic components are densely mounted on a circuit board for small components, high heat dissipation (thermal conductivity) is also required to prevent malfunctions caused by heat from high heat dissipation components.

[0030] The resin composition of the present invention has the above-mentioned structure, so it has excellent low dielectric properties and heat dissipation. Therefore, when it is suitable for use in a circuit substrate, even if it is used in a high-frequency band, energy loss is small, and since it is difficult for mounted components such as IC to store heat, stable communication is possible.

[0031] In addition, the resin composition of the present invention is also excellent in moldability, low thermal expansion, toughness, and heat resistance.

[0032] The resin composition of the present invention comprises a melt-processable fluororesin. Compared with a resin composition comprising a non-melt-processable fluororesin (e.g., a resin composition comprising polytetrafluoroethylene as described in U.S. Patent Application Publication No. 2019 / 0136109), the resin composition of the present invention has excellent moldability, for example, it can be easily processed into a sheet or film shape suitable for a circuit board because it can be extruded.

[0033] In this specification, melt-processable means that the polymer can be melted and processed using existing processing equipment such as an extruder and an injection molding machine.

[0034] The fluororesin preferably has a melting point of 100 to 360°C, more preferably 140 to 350°C, and even more preferably 160 to 320°C.

[0035] In this specification, the melting point is a temperature corresponding to the maximum value in the heat of fusion curve when the temperature is increased at a rate of 10° C. / min using a differential scanning calorimeter [DSC].

[0036] The fluororesin preferably has a melt flow rate (MFR) of 10 g / 10 min or more, more preferably 20 g / 10 min or more, and preferably 200 g / 10 min or less, more preferably 100 g / 10 min or less.

[0037] The MFR of the fluororesin is a value obtained by measuring the mass (g / 10 minutes) of the polymer flowing out from a nozzle having an inner diameter of 2 mm and a length of 8 mm at a measurement temperature (for example, 372° C. in the case of PFA and FEP described below, and 297° C. in the case of ETFE) and a load (for example, 5 kg in the case of PFA, FEP and ETFE) determined according to ASTM D1238 using a melt flow indexer.

[0038] Examples of the fluororesins include tetrafluoroethylene [TFE] / perfluoro(alkyl vinyl ether) [PAVE] copolymers [PFA], TFE / hexafluoropropylene [HFP] copolymers [FEP], ethylene [Et] / TFE copolymers [ETFE], Et / TFE / HFP copolymers [EFEP], polychlorotrifluoroethylene [PCTFE], chlorotrifluoroethylene [CTFE] / TFE copolymers, Et / CTFE copolymers, polyvinyl fluoride [PVF], polyvinylidene fluoride [PVDF], and the like.

[0039] Among them, the fluororesin is preferably at least one selected from the group consisting of PFA, FEP, and ETFE, more preferably at least one selected from the group consisting of PFA and FEP, and even more preferably PFA.

[0040] The above-mentioned fluororesin is also preferably a perfluororesin.

[0041] PFA is not particularly limited, but is preferably a copolymer in which the molar ratio of TFE units to PAVE units (TFE units / PAVE units) is 70 / 30 or more and less than 99 / 1. A more preferred molar ratio is 70 / 30 or more and 98.9 / 1.1 or less, and a further preferred molar ratio is 80 / 20 or more and 98.9 / 1.1 or less. If the TFE unit is too little, the mechanical properties tend to decrease, and if it is too much, the melting point tends to become too high and the moldability tends to decrease. The above-mentioned PFA is also preferably a copolymer in which the monomer units from monomers copolymerizable with TFE and PAVE are 0.1 to 10 mol%, and the total of TFE units and PAVE units is 90 to 99.9 mol%. As monomers copolymerizable with TFE and PAVE, HFP, CZ 3 Z 4 =CZ 5 (CF2) n Z 6 (Where Z 3 , Z 4 and Z 5 are the same or different, representing a hydrogen atom or a fluorine atom, Z 6 represents a hydrogen atom, a fluorine atom or a chlorine atom, and n represents an integer of 2 to 10. ) a vinyl monomer represented by, and CF2=CF-OCH2-Rf 7 (Where Rf 7 represents a perfluoroalkyl group having 1 to 5 carbon atoms. ) and the like;

[0042] The melting point of the PFA is preferably 180°C or higher and lower than 324°C, more preferably 230 to 320°C, and even more preferably 280 to 320°C.

[0043] As FEP, there is no particular limitation, but preferably a copolymer in which the molar ratio of TFE units to HFP units (TFE units / HFP units) is 70 / 30 or more and less than 99 / 1. A more preferred molar ratio is 70 / 30 or more and 98.9 / 1.1 or less, and a further preferred molar ratio is 80 / 20 or more and 98.9 / 1.1 or less. If the TFE unit is too little, there is a tendency for the mechanical properties to decrease, and if there is too much, there is a tendency for the melting point to become too high and the moldability to decrease. The above-mentioned FEP is also preferably a copolymer in which the monomer units from monomers copolymerizable with TFE and HFP are 0.1 to 10 mol%, and the total of TFE units and HFP units is 90 to 99.9 mol%. As monomers copolymerizable with TFE and HFP, PAVE, alkyl perfluorovinyl ether derivatives, etc. can be cited.

[0044] The melting point of the FEP is lower than that of the PTFE, and is preferably 150°C or higher and lower than 324°C, more preferably 200 to 320°C, and even more preferably 240 to 320°C.

[0045] As ETFE, it is preferred that the molar ratio of TFE unit to ethylene unit (TFE unit / ethylene unit) is 20 / 80 or more and 90 / 10 or less. A more preferred molar ratio is 37 / 63 or more and 85 / 15 or less, and a further preferred molar ratio is 38 / 62 or more and 80 / 20 or less. ETFE can also be a copolymer consisting of TFE, ethylene, and a monomer copolymerizable with TFE and ethylene. As a copolymerizable monomer, the following formula can be cited:

[0046] CH2=CX 5 R 3 , CF2=CFRf 3 CF2=CFORf 3 , CH2=C(Rf 3 )2

[0047] (Where X 5 represents a hydrogen atom or a fluorine atom, Rf 3 represents a fluorinated alkyl group which may or may not contain an ether bond. ) The monomer represented by , among which CF2=CFRf is preferred 3 CF2=CFORf 3 and CH2=CX 5 R 3 The fluorine-containing vinyl monomer represented by is more preferably HFP, CF2=CF-ORf 4 (Where Rf 4 represents a perfluoroalkyl group having 1 to 5 carbon atoms. The perfluoro(alkyl vinyl ether) represented by Rf 3 It is a fluorinated alkyl group having 1 to 8 carbon atoms, CH2=CX5 R 3 The fluorine-containing vinyl monomer represented by the above. In addition, as the monomer copolymerizable with TFE and ethylene, it can be an aliphatic unsaturated carboxylic acid such as itaconic acid and itaconic anhydride. The monomer copolymerizable with TFE and ethylene is preferably 0.1 to 10 mol%, more preferably 0.1 to 5 mol%, and particularly preferably 0.2 to 4 mol% relative to the fluorine-containing polymer.

[0048] The melting point of the ETFE is preferably 140°C or higher and lower than 324°C, more preferably 160 to 320°C, and even more preferably 195 to 320°C.

[0049] The content of each monomer unit of the above-mentioned copolymer can be calculated by appropriately combining NMR, FT-IR, elemental analysis, and fluorescent X-ray analysis according to the types of monomers.

[0050] From the viewpoint of adhesion to the metal layer, the fluororesin may have a carbonyl-containing functional group in the main chain skeleton.

[0051] Examples of the functional groups include carbonate groups, carboxylic acid halide groups (haloformyl groups), formyl groups, carboxyl groups, ester groups [-C(=O)O-], anhydride groups [-C(=O)OC(=O)-], isocyanate groups, amide groups, imide groups [-C(=O)-NH-C(=O)-], carbamate groups [-NH-C(=O)O-], carbamoyl groups [NH2-C(=O)-], carbamoyloxy groups [NH2-C(=O)O-], urea groups [NH2-C(=O)-NH-], aminooxalyl groups [NH2-C(=O)-C(=O)-] and other parts of the chemical structure.

[0052] The hydrogen atom bonded to the nitrogen atom of an amide group, an imide group, a carbamate group, a carbamoyl group, a carbamoyloxy group, a urea group, an aminooxalyl group or the like may be substituted with a hydrocarbon group such as an alkyl group.

[0053] The functional group is preferably at least one selected from the group consisting of a carboxyl group, an ester group, and an isocyanate group, from the viewpoint of excellent adhesion to the metal layer. Among these, a carboxyl group is particularly preferred.

[0054] From the viewpoint of adhesion to the metal layer, the fluororesin is preferably 6 The number of carbon atoms in the main chain is 5 or more. From the perspective of better adhesion, the number of carbon atoms in the main chain is more preferably 10 6 The number of carbon atoms in the main chain is preferably 20 or more, more preferably 50 or more, particularly preferably 80 or more, and particularly preferably 100 or more. 6The number of carbon atoms in the main chain is 8000 or less, more preferably 1000 or less.

[0055] It should be noted that the method for producing a fluororesin having a carbonyl-containing functional group in the above ratio is not particularly limited. As a method for introducing the above functional group into the fluororesin, it can be carried out by any known method such as a method of forming a terminal from an initiator, a method of using a monomer having the above functional group as a source of the functional group as a monomer of the third component, and a method of combining structural units having the above functional group by a graft reaction.

[0056] The carbonyl-containing functional group can be adjusted to fall within the above range by appropriately combining the above methods.

[0057] For example, the amount of the carbonyl-containing functional group formed as the terminal of the initiator can be a predetermined value according to the selection of the initiator during polymerization, the mixing amount, the addition method, etc. When other methods are used, the amount of the functional group can also be a predetermined value according to the amount of the monomer having the functional group as the functional group source, the reaction amount of the graft reaction, etc.

[0058] The number of functional groups containing a carbonyl group is measured by the following method.

[0059] The sample was compression molded at 350°C to produce a film with a thickness of 0.25 to 0.3 mm. The film was scanned 40 times with a Fourier transform infrared spectrometer [FT-IR] (trade name: 1760X, manufactured by Perkin Elmer) to obtain an infrared absorption spectrum and a differential spectrum from the background spectrum after complete fluorination without the presence of terminal groups. From the absorption peak of the carbonyl group shown in the differential spectrum, the following formula was used to calculate the carbonyl group per 1×10 6 The number of carbonyl-containing functional groups N per carbon atom.

[0060] N=I×K / t

[0061] I: Absorbance

[0062] K: Correction coefficient

[0063] t: film thickness (mm)

[0064] The content of the fluororesin is preferably 35 to 70% by mass relative to the resin composition, preferably 45% by mass or more, more preferably 48% by mass or more, further preferably 50% by mass or more, and preferably 65% ​​by mass or less, more preferably 62% by mass or less.

[0065] The boron nitride particles contained in the resin composition are preferably particles of hexagonal boron nitride (hBN).

[0066] The boron nitride particles contained in the resin composition preferably have a 50% particle size (D50) of 3.0 μm or less, more preferably 2.8 μm or less, and preferably 2.0 μm or more, more preferably 2.2 μm or more.

[0067] Thus, each characteristic of the above-mentioned resin combination can be further improved. Especially, the MFR of the above-mentioned resin combination can be made within the scope described later, and the above-mentioned resin combination becomes a resin combination with more excellent formability. In addition, due to the reduction of the ratio of relatively large particles, stress can be dispersed, the tensile fracture strain of the above-mentioned resin combination can be improved, and toughness can be improved.

[0068] The 50% particle size can be determined from the particle size distribution measured using a laser diffraction particle size distribution measuring apparatus.

[0069] In this specification, the particle size distribution of the boron nitride particles is measured under the following conditions using a laser diffraction particle size distribution measuring apparatus (RODOS T4.1 manufactured by Sympatec GmbH).

[0070] (Measurement conditions)

[0071] Measuring range: R1 (0.18~35μm)

[0072] Dispersion pressure: 3bar

[0073] Sample size: 1g

[0074] The boron nitride particles contained in the resin composition preferably have a 90% particle size (D90) of 9.0 μm or less, more preferably 8.0 μm or less, and further preferably 7.0 μm or less. Also, the 90% particle size is preferably 3.0 μm or more, more preferably 4.0 μm or more, and further preferably 5.0 μm or more.

[0075] This can further improve various properties of the resin composition, and in particular, can achieve both heat dissipation and moldability of the resin composition at a higher level.

[0076] The 90% particle size can be determined from the particle size distribution measured using a laser diffraction particle size distribution measuring apparatus.

[0077] The boron nitride particles contained in the resin composition preferably have a particle size of 14.6 to 20.6 μm and a ratio (a) of 5.0% or less, more preferably 4.0% or less, further preferably 3.0% or less, further more preferably 2.0% or less, and particularly preferably 1.0% or less. In addition, the ratio (a) may be 0.01% or more.

[0078] This can further improve various properties of the resin composition, and in particular, can achieve both heat dissipation and moldability of the resin composition at a higher level.

[0079] The above ratio (a) can be obtained from the particle size distribution measured using a laser diffraction particle size distribution measuring apparatus.

[0080] The boron nitride particles contained in the resin composition preferably have a particle size of 24.6 to 29.4 μm and a ratio (b) of 10.0% or less, more preferably 5.0% or less, further preferably 2.0% or less, and particularly preferably 1.5% or less. Alternatively, the ratio (b) may be 0.1% or more.

[0081] This can further improve various properties of the resin composition, and in particular, can achieve both heat dissipation and moldability of the resin composition at a higher level.

[0082] The ratio (b) can be determined from the particle size distribution measured using a laser diffraction particle size distribution measuring apparatus.

[0083] For the boron nitride particles contained in the above-mentioned resin composition, it is preferred that the ratio (b) of the particles having a particle size of 24.6 to 29.4 μm relative to the ratio (a) of the particles having a particle size of 14.6 μm to 20.6 μm is 1.0 or more, more preferably 1.1 or more. In addition, the above-mentioned ratio is preferably 20.0 or less, more preferably 10.0 or less, and further preferably 5.0 or less.

[0084] Thus, the various properties of the resin composition can be further improved. In particular, the MFR of the resin composition can be within the range described below, and the resin composition becomes a resin composition with better moldability. In addition, since relatively large particles with a particle size of 24.6 to 29.4 μm that contribute to thermal conductivity exist to some extent, the thermal conductivity of the resin composition can be improved, and the heat dissipation can be improved.

[0085] The above ratio can be calculated based on the ratios (a) and (b) obtained from the particle size distribution measured using a laser diffraction particle size distribution measuring apparatus.

[0086] The boron nitride particles contained in the resin composition preferably do not substantially contain particles having a particle size of 35.0 μm or more, and more preferably do not substantially contain particles having a particle size of 30.0 μm or more.

[0087] This can further improve various properties of the resin composition, and in particular, can achieve both heat dissipation and moldability of the resin composition at a higher level.

[0088] The boron nitride particles substantially do not contain particles within the above-mentioned particle size range, which means that the proportion of particles within the above-mentioned particle size range in the particle size distribution measured using a laser diffraction particle size distribution measuring apparatus is 0.1% or less.

[0089] When the particle size distribution of the boron nitride particles in the resin composition is within the above-mentioned ranges, the boron nitride particles can be densely present in the resin composition, and the increase of melt viscosity can be suppressed. In addition, because there are large boron nitride particles to a certain extent, excellent thermal conductivity is embodied. As a result, a resin composition (excellent moldability) with excellent heat dissipation and maintained fluidity is prepared.

[0090] In the present specification, the particle size distribution of the boron nitride particles in the resin composition may be a result of measuring the boron nitride particles remaining after the resin composition is incinerated.

[0091] The content of the boron nitride particles is preferably 30 to 65% by mass relative to the resin composition, preferably 35% by mass or more, more preferably 38% by mass or more, and preferably 60% by mass or less, more preferably 55% by mass or less.

[0092] When the content of the boron nitride particles is within the above range, the low dielectric properties and heat dissipation properties of the resin composition are further improved.

[0093] Conventionally, when a large amount of boron nitride particles are mixed with a fluororesin, the melt viscosity tends to become extremely high, making molding difficult. However, even when a relatively large amount of boron nitride particles is contained as described above, the resin composition of the present invention has excellent moldability.

[0094] The resin composition preferably has a melt flow rate (MFR) of 5.0 g / 10 minutes or more. The resin composition having an MFR within the above range has excellent moldability, and in particular has moldability that enables injection molding and extrusion molding.

[0095] The MFR of the resin composition is preferably 7.0 g / 10 min or more, more preferably 10.0 g / 10 min or more, and preferably 100 g / 10 min or less, more preferably 70 g / 10 min or less, and further preferably 50 g / 10 min or less.

[0096] The MFR of the resin composition is a value measured in accordance with ASTM D-1238 using a die having a diameter of 2.1 mm and a length of 8 mm under a load of 5 kg and at 372°C.

[0097] In one preferred embodiment, the melt-processable fluororesin accounts for 35 to 70% by mass, the boron nitride particles account for 30 to 65% by mass, and the resin composition has a melt flow rate of 5.0 g / 10 minutes or more.

[0098] The resin composition of the present invention may also contain other components as required. As the above-mentioned other components, there are no particular limitations, but fibrous reinforcing materials such as whiskers of potassium titanate, glass fibers, asbestos fibers, carbon fibers, ceramic fibers, potassium titanate fibers, aramid fibers, and other high-strength fibers; inorganic fillers such as talc, mica, clay, carbon powder, graphite, and glass beads; colorants; commonly used inorganic or organic fillers such as flame retardants; lubricants such as silicone oil and molybdenum disulfide; pigments; conductive agents such as carbon black; impact resistance enhancers such as rubber; lubricants such as magnesium stearate; ultraviolet absorbers such as benzotriazole compounds; other additives, etc. can be used.

[0099] These additives may be mixed within a range not impairing the effects of the above-mentioned resin composition.

[0100] The resin composition of the present invention can be produced, for example, by mixing the above-mentioned fluororesin, the above-mentioned boron nitride particles, and other components as required. The above-mentioned mixing can be performed using a single-screw or twin-screw extruder or the like.

[0101] From the viewpoint of being able to further improve various properties, it is preferred to obtain the resin composition by melt kneading.

[0102] When the above-mentioned resin composition is obtained by melt-kneading, it is preferred to use aggregate particles of boron nitride as the raw material boron nitride particles. By melt-kneading such raw material boron nitride particles together with the above-mentioned fluororesin, the MFR of the obtained resin composition can be easily controlled within the above-mentioned range. In addition, the particle size distribution of the boron nitride particles in the obtained resin composition can also be easily controlled within the above-mentioned preferred range.

[0103] The above-mentioned aggregate particles are formed by aggregation of primary particles of boron nitride.

[0104] The aspect ratio (longer diameter / shorter diameter) of the raw material boron nitride particles is preferably 1.0 to 3.0, more preferably 1.0 to 2.5.

[0105] The aspect ratio can be calculated from the major axis and minor axis measured using a scanning electron microscope (SEM), and the average value of the aspect ratios measured for 30 samples is used.

[0106] Specific examples of the raw material boron nitride particles include UHP-G1H manufactured by Showa Denko K.K., CF600 manufactured by Momentive, and FS-3 manufactured by Mizushima Iron Alloy Co., Ltd.

[0107] The temperature of the melt kneading is preferably higher than the melting point of the fluororesin, and more preferably 5° C. or more higher than the melting point of the fluororesin.

[0108] The resin composition may be in the form of powder, granules, pellets or the like, but is preferably in the form of pellets from the viewpoint of easy molding.

[0109] The resin composition of the present invention preferably has a relative dielectric constant of 3.2 or less at 6 GHz and 25° C., more preferably 3.0 or less, and even more preferably 2.8 or less. The lower limit is not particularly limited, and may be 2.0.

[0110] The relative dielectric constant was measured in accordance with ASTM D 150 at 6 GHz and 25° C. using a cavity resonator dielectric constant measuring apparatus (manufactured by Agilent Technologies).

[0111] The resin composition of the present invention preferably has a dielectric loss tangent of 11×10 -4 Below, more preferably 10×10 -4 Below, more preferably 9.0×10 -4 The lower limit is not particularly specified, but can be 0.1×10 -4 .

[0112] The dielectric loss tangent was measured in accordance with ASTM D 150 at 6 GHz and 25° C. using a cavity resonator dielectric constant measuring apparatus (manufactured by Agilent Technologies).

[0113] The resin composition of the present invention preferably has a thermal conductivity of 1.5 W / m·K or more, more preferably 2.0 W / m·K or more, further preferably 2.5 W / m·K or more, and particularly preferably 3.0 W / m·K or more. If the thermal conductivity is within the above range, the resin composition has a better heat dissipation property.

[0114] The thermal conductivity can be calculated from the product of the thermal diffusivity, the specific heat capacity, and the density measured by the following method.

[0115] (Thermal diffusivity)

[0116] Device: Thermowave Analyzer TA33 manufactured by BETHEL

[0117] Method: Cycle heating radiation temperature method

[0118] Measurement temperature: 25℃

[0119] The measurement was performed in the thickness direction and in-plane direction of the sample prepared by the following method.

[0120] Sample: 0.5mm t plate obtained by compression molding

[0121] The measurements were performed assuming that N=3, and the average value was used.

[0122] ※ Sample molding conditions

[0123] Equipment: IMC-11FA heat press machine manufactured by Imoto Manufacturing Co., Ltd.

[0124] Molding temperature: 360℃

[0125] Pressure: 10MPa

[0126] Pressurization time: 2 minutes

[0127] (Specific heat capacity)

[0128] The measurement was performed in accordance with JIS K7123, and the value at 25°C was adopted.

[0129] (density)

[0130] The measurement was carried out in accordance with JIS Z 8807.

[0131] The resin composition of the present invention is preferably a material that can be used to obtain a test piece in accordance with ASTM D 790 by injection molding at a barrel temperature of 380° C. and a mold temperature of 200° C. using a 15t injection molding machine (manufactured by Sumitomo Heavy Industries, Ltd., M26 / 15B). Such a resin composition has excellent injection moldability. Therefore, it can also be extruded and easily processed into the shape of a sheet or film.

[0132] The resin composition of the present invention preferably has a tensile strain at break of 1.0% or more, more preferably 1.1% or more. When the tensile strain at break is within the above range, the toughness of the resin composition is further improved.

[0133] The tensile fracture strain can be measured by performing a tensile test on a test piece using Type V in accordance with ASTM D 638.

[0134] The resin composition of the present invention can be used for a circuit substrate, and is preferably used in an insulating layer of a circuit substrate.

[0135] As the circuit substrate, a printed wiring substrate is preferred. The printed wiring substrate may be a rigid substrate, a flexible substrate, or a rigid-flexible substrate.

[0136] The circuit substrate is preferably a high-frequency circuit substrate. A high-frequency circuit substrate is a circuit substrate that can operate even in a high-frequency band. The high-frequency band may be a band above 1 GHz, preferably a band above 3 GHz, and more preferably a band above 5 GHz. The upper limit is not particularly limited, and may be a band below 100 GHz.

[0137] The resin composition of the present invention has low dielectric properties and excellent thermal conductivity, and therefore can provide a circuit board having low transmission loss even in a high frequency band and excellent heat dissipation properties.

[0138] The resin composition of the present invention can also be suitably used for a circuit board for a fifth-generation mobile communication system.

[0139] The present invention also relates to a molded article for a circuit board obtained from the resin composition of the present invention. The molded article of the present invention is obtained from the resin composition of the present invention, and therefore has excellent low dielectric properties, heat dissipation, low thermal expansion, toughness, and heat resistance.

[0140] The molded article of the present invention can be obtained by molding the resin composition of the present invention.

[0141] The method for molding the resin composition is not particularly limited, and examples thereof include injection molding, extrusion molding, compression molding, blow molding, film molding, wire coating molding, etc. The resin composition of the present invention has excellent fluidity and can be appropriately molded by injection molding or extrusion molding.

[0142] The shape of the molded body is not particularly limited, and the molded body may be formed into various shapes such as a sheet, a film, a strip, or a tube.

[0143] The above-mentioned molded product is preferably a sheet or a film.

[0144] The molded body may be surface-modified on one or both sides. Surface modification is preferred from the viewpoint of improving adhesion with a metal layer such as copper foil.

[0145] The specific method of the above-mentioned surface modification is not particularly limited, and any known method can be used for the surface modification. Specifically, a discharge treatment such as a corona discharge treatment, a glow discharge treatment, a plasma discharge treatment, or a sputtering treatment can be used. For example, by introducing oxygen, nitrogen, hydrogen, etc. into the discharge atmosphere, in addition to being able to control the surface free energy, the surface to be modified can be exposed to an inert gas (such as nitrogen, helium, argon, etc.) atmosphere containing an organic compound, and a high-frequency voltage is applied between the electrodes to cause a discharge, thereby generating active species on the surface, and then the surface modification is performed by introducing functional groups of organic compounds or grafting polymerizing polymerizable organic compounds.

[0146] The surface modification is particularly suitable when the molded article is a sheet or a film.

[0147] The molded article of the present invention can be suitably used as, for example, an insulating layer of a circuit board.

[0148] The present invention relates to a laminate for a circuit board, comprising a metal layer (A1) and a layer (B) formed from the above-mentioned resin composition of the present invention.

[0149] The metal constituting the metal layer (A1) is preferably at least one selected from the group consisting of copper, stainless steel, aluminum, iron, and alloys thereof, more preferably at least one selected from the group consisting of copper, stainless steel, and aluminum, and further preferably copper.

[0150] Examples of the stainless steel include austenitic stainless steel, martensitic stainless steel, and ferritic stainless steel.

[0151] The metal layer (A1) may be a layer formed by sputtering, vacuum deposition, electroplating, electroless plating, or the like, or may be a layer formed of a metal foil.

[0152] When the metal layer (A1) is a layer formed of a metal foil, the metal foil can be bonded to the layer (B) by hot pressing to form the metal layer (A1).

[0153] The thickness of the metal layer (A1) may be, for example, 2 to 200 μm, and preferably 5 to 50 μm.

[0154] The metal layer (A1) may be provided on only one surface of the layer (B) or on both surfaces.

[0155] The layer (B) is formed from the resin composition of the present invention. As the layer (B), the above-mentioned molded product of the present invention can be used.

[0156] The layer (B) is preferably a sheet or film formed from the resin composition of the present invention.

[0157] The above-mentioned surface modification may be performed on one side or both sides of the layer (B).

[0158] The thickness of the layer (B) may be, for example, 1 μm to 1 mm, preferably 1 to 500 μm, more preferably 150 μm or less, and even more preferably 100 μm or less.

[0159] The laminate may further include a layer other than the metal layer (A1) and the layer (B).

[0160] The laminate of the present invention can be preferably used as, for example, a metal-clad laminate for forming a circuit board.

[0161] The present invention also relates to a circuit board comprising a metal layer (A2) and a layer (B) formed from the above-mentioned resin composition of the present invention.

[0162] Examples of the metal constituting the metal layer (A2) include the same metals as those constituting the metal layer (A1), and the thickness is also the same.

[0163] The layer (B) is the same as the layer (B) in the laminate of the present invention.

[0164] The metal layer (A2) constitutes a circuit. The method for forming the circuit pattern is not particularly limited, and examples thereof include a method of forming an unpatterned metal layer on the layer (B) and then patterning it by etching, a method of directly forming a metal layer at a location where the circuit pattern on the layer (B) is required, and a method of combining the two. In either case, existing known methods can be used.

[0165] The circuit board of the present invention may be a board obtained by patterning the metal layer (A1) in the laminate of the present invention.

[0166] The metal layer (A2) may be provided on only one side of the layer (B) or on both sides. In addition, the circuit substrate may further include a layer other than the metal layer (A2) and the layer (B). In addition, the surface modification may be performed on one side or both sides of the layer (B).

[0167] The circuit board of the present invention is preferably a printed wiring board. The printed wiring board is as described above.

[0168] The circuit board of the present invention is also preferably a high-frequency circuit board. The high-frequency circuit board is as described above.

[0169] The circuit board of the present invention is also preferably a circuit board for a fifth-generation mobile communication system.

[0170] Example

[0171] Next, the present invention will be described in further detail with reference to examples, but the present invention is not limited to these examples.

[0172] The physical properties of Examples and Comparative Examples were measured by the following methods.

[0173] Thermal conductivity

[0174] It is calculated from the product of the thermal diffusivity, specific heat capacity and density measured by the following method.

[0175] (Thermal diffusivity)

[0176] Device: Thermowave Analyzer TA33 manufactured by BETHEL

[0177] Method: Cycle heating radiation temperature method

[0178] Measurement temperature: 25℃

[0179] The measurement was performed in the thickness direction and in-plane direction of the sample prepared by the following method.

[0180] Sample: 0.5mm t plate obtained by compression molding

[0181] The measurements were performed assuming that N=3, and the average value was used.

[0182] ※ Sample molding conditions

[0183] Equipment: IMC-11FA heat press machine manufactured by Imoto Manufacturing Co., Ltd.

[0184] Molding temperature: 360℃

[0185] Pressure: 10MPa

[0186] Pressurization time: 2 minutes

[0187] (Specific heat capacity)

[0188] The measurement was performed in accordance with JIS K 7123, and the value at 25°C was adopted.

[0189] (density)

[0190] The measurement was carried out in accordance with JIS Z 8807.

[0191] Relative dielectric constant and dielectric loss tangent

[0192] The dielectric constant was measured in accordance with ASTM D 150 at 6 GHz and 25° C. using a cavity resonator dielectric constant measuring apparatus (Network analyzer system manufactured by Agilent Technologies).

[0193] Linear expansion coefficient

[0194] The measurement was conducted in accordance with JIS K7177.

[0195] MFR

[0196] The melt index was determined according to ASTM D 1238 as the mass (g / 10 minutes) of the polymer flowing out from a nozzle having an inner diameter of 2 mm and a length of 8 mm at 372° C. and a load of 5 kg per 10 minutes using a melt flow indexer.

[0197] Particle size distribution of boron nitride particles in resin composition

[0198] 5 g of the pellets of the resin composition were placed in a nickel crucible and heated at 600° C. for 2 hours in an electric muffle furnace (manufactured by ADVANTEC, FUW222PA) to burn out the resin and obtain an ash residue.

[0199] The obtained residue was measured under the following conditions using a laser diffraction particle size distribution measuring apparatus (RODOS T4.1 manufactured by Sympatec GmbH).

[0200] (Measurement conditions)

[0201] Measuring range: R1 (0.18~35μm)

[0202] Dispersion pressure: 3bar

[0203] Sample size: 1g

[0204] The following raw materials were used in Examples and Comparative Examples.

[0205] (Fluororesin)

[0206] PFA1: tetrafluoroethylene / perfluoro(alkyl vinyl ether) copolymer, MFR=72g / 10min

[0207] (Boron Nitride)

[0208] BN1: UHP-G1H manufactured by Showa Denko K.K., aggregated boron nitride particles, average particle size 50 μm

[0209] Example 1

[0210] A resin composition was prepared by melt-kneading 60 parts by mass of fluororesin (PFA1) and 40 parts by mass of boron nitride (BN1). The melt-kneading was carried out at 380°C using a twin-screw extruder (MFU20TW manufactured by Technovel). Boron nitride was supplied from a side feeder. The obtained resin composition was evaluated. The results are shown in Table 1.

[0211] Example 2

[0212] Resin compositions were prepared and evaluated in the same manner as in Example 1 except that the amounts of the fluororesin and boron nitride were changed as shown in Table 1. The results are shown in Table 1.

[0213] Comparative Example 1

[0214] PFA1 was used alone and the evaluation was carried out in the same manner as in Example 1. The results are shown in Table 1.

[0215] [Table 1]

[0216]

[0217] It is found that Examples 1 and 2 can reduce the dielectric loss tangent while suppressing an increase in the relative dielectric constant (dielectric constant) compared to Comparative Example 1, and are also excellent in thermal conductivity and other characteristics.

Claims

1. A circuit board, which is obtained from a resin composition comprising a melt-processable fluororesin and boron nitride particles, wherein: The content of the boron nitride particles is 38% to 65% by mass relative to the resin composition. In the boron nitride particles, the ratio (b) of the particles having a particle size of 24.6 μm to 29.4 μm to the ratio (a) of the particles having a particle size of 14.6 μm to 20.6 μm, that is, (b) / (a) is 1.0 or more, The ratio (a) is 0.01% to 5.0%, and the ratio (b) is 0.1% to 10.0%. The 90% particle size, namely D90, is 9.0 μm or less.

2. The circuit substrate according to claim 1, wherein: The melt-processible fluororesin is at least one selected from the group consisting of tetrafluoroethylene / perfluoro(alkyl vinyl ether) copolymers, tetrafluoroethylene / hexafluoropropylene copolymers, and ethylene / tetrafluoroethylene copolymers. 3 . The circuit board according to claim 1 , comprising a molded body obtained from the resin composition. 4 . The circuit board according to claim 1 , which is obtained from a laminate comprising a metal layer (A1) and a layer (B) formed from the resin composition. 5 . The circuit board according to claim 1 , comprising a metal layer (A2) and a layer (B) formed from the resin composition.

6. The circuit substrate according to claim 1 or 2, wherein: The circuit substrate is a printed wiring substrate.

7. The circuit substrate according to claim 1 or 2, wherein: The circuit substrate is a high-frequency circuit substrate.

8. The circuit substrate according to claim 1 or 2, wherein: The circuit substrate is a circuit substrate for a fifth generation mobile communication system.

Citation Information

Patent Citations

  • Resin composition for dielectric and high-frequency dielectric device

    JP2015168731A

  • Dielectric layer with improved thermally conductivity

    US20190136109A1

  • Dielectric layer with improved thermally conductivity

    WO2019094238A1

  • Resin composition and molded article

    WO2020045260A1